2001
DOI: 10.4049/jimmunol.167.7.3610
|View full text |Cite
|
Sign up to set email alerts
|

Bm1–Bm5 Classification of Peripheral Blood B Cells Reveals Circulating Germinal Center Founder Cells in Healthy Individuals and Disturbance in the B Cell Subpopulations in Patients with Primary Sjögren’s Syndrome

Abstract: Analyses of B cells in the bone marrow and secondary lymphoid tissues have revealed a broad range of cell surface markers defining B cell subpopulations, but only a few of these have been used to analyze B cell subpopulations in peripheral blood (PB). We report here the delineation of circulating PB B cell subpopulations by staining for CD19, CD38, and IgD in combination with CD10, CD44, CD77, CD95, CD23, IgM, and the B cell memory marker CD27. The utility of this approach is shown by the demonstration of dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
276
1
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(312 citation statements)
references
References 48 publications
29
276
1
5
Order By: Relevance
“…Recent studies have shown disturbances in peripheral B cell populations in primary SS, with significantly enhanced CD27Ϫ naive and diminished CD27ϩ memory B cells (6,8,9). This was confirmed in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Recent studies have shown disturbances in peripheral B cell populations in primary SS, with significantly enhanced CD27Ϫ naive and diminished CD27ϩ memory B cells (6,8,9). This was confirmed in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…The frequency of peripheral CD27ϩ,CD19ϩ memory B cells was significantly reduced in patients with primary SS compared with healthy control subjects (mean Ϯ SD 13.3 Ϯ 12.3% versus 25.6 Ϯ 7.2%; P Յ 0.0014), whereas the frequency of CD19ϩ,CD27Ϫ naive B cells was significantly enhanced in patients with primary SS (mean Ϯ SD 86.1 Ϯ 12.0% versus 74.4 Ϯ 7.2%; P Յ 0.0014) as reported previously (6,8,9). To ensure that these alterations in patients with primary SS did not further influence the analyses, either CD19ϩ,CD27Ϫ or CD19ϩ,CD27ϩ B cells were gated, and the chemokine receptor expression was subsequently analyzed within each subpopulation ( Figures 1A and B).…”
Section: Chemokine Receptors On B Cells In Primary Ss 2111supporting
confidence: 83%
See 1 more Smart Citation
“…Several studies have suggested that these B cells can also be detected in the PB of normal individuals, as well as patients with SLE (19,53). Interestingly, the frequency of such cells in normal individuals is similar to that of transitional B cells; ϳ2-3% (53).…”
Section: Discussionmentioning
confidence: 98%
“…A population of B cells in human tonsil has been described as pre-GC or GC founder cells (19,52,53). Several studies have suggested that these B cells can also be detected in the PB of normal individuals, as well as patients with SLE (19,53).…”
Section: Discussionmentioning
confidence: 99%